New opportunities for research on food security - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Dominique Charron from the International Research Center says that #AASW6 is a place for new opportunities for research on food security problems. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/